Cortico-cancellous osseointegration into additively manufactured titanium implants using a load-bearing femoral ovine model - Feldman, Adam; Assad, Michel; Davies, Mark B.; Mangwani, Jitendra; Alabort, Enrique; Tuncer, Mac (Frontiers in Bioengineering and Biotechnology, 2024)
Titanium-based implants can be used to fill voids in bone reconstruction surgery. Through additive manufacturing (AM), it is possible to produce titanium implants with osteoconductive properties such as high porosity and low stiffness. AM facilitates a level of design flexibility and personalisation that is not feasible with traditional techniques. In this study, osseointegration into titanium alloy (Ti-6Al-4V) lattices was investigated for 12 weeks post-implantation using a novel bicortical load-bearing ovine model. The objective was to assess the safety and efficacy of AMfabricated implants using two lattice structures of contrasting stiffness spanning the full width of the femoral condyle. This was achieved by evaluating implant osseointegration and bone-implant contact properties by histomorphometry, scoring local implant tissue responses via histopathology, and micro-computed tomography reconstruction. We found that Ti-6Al-4V implants facilitated widespread and extensive osseointegration, with bone maturation ongoing at the conclusion of the trial period. Following the implantation period, no adverse clinical indications that could be directly ascribed to the presence of the implanted device were identified as determined by macroscopic and microscopic observation.